Absenteeism, pension reforms and grandmothers - Flavia Coda Moscarola; Elsa Fornero; Steinar Strøm (Institute for the Study of Labor (IZA), 2015)
Both economic and epidemiological literature have shown that perceived high strain at work and lack of social infrastructures are good predictors of sick-leave. The latter is particularly relevant in (Mediterranean) countries where facilities for children and LTC services are relatively scarce and women are frequently asked to fill the gap. The Italian 2011 pension reform, approved under the threat of a financial crisis, significantly restricted age and seniority requirements for retirement, especially for women in private employment, who still enjoyed a much more favorable treatment than men and women in public service. We investigate whether older Italian women (still in employment) reacted to the postponement of retirement by increasing their recourse to sick-leave. The empirical analysis, based on a noteworthy administrative data set provided by the Italian Social Security Agency, offers unequivocal evidence that this has indeed been the case, in particular for grandmothers. This result lends itself to interesting policy considerations.
Keywords: J26; J13; C33; 330; pension reform; sick-leave; child-care